VARIABEL KEUANGAN YANG MEMBEDAKAN TINGKAT LIKUIDITAS BANK UMUM DI BURSA EFEK INDONESIA - AMBARAWATI, A.A.AYU DIAH; Bagus Wiksuana, I Gusti; Sri Artini, Luh Gede (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.06.NO.12.TAHUN 2017, 2017)
This research developed a research model that aims to explain financial ratio that can differentiate the liquidity level of commercial banks, and identify the financial ratios which among the financial ratios that sever the most dominant to sever the liquidity level of banks listed on the IDX period 2010-2014. The independent variables in the research are bank financial ratios of bank size, NWC, CAR, ROA, ROE and NPL. Dependent variable used in this research is liquidity ratio with Loan to Deposit Ratio (LDR) indicator. The data analysis in this research  uses discriminant analysis technique. Based on discriminant test with simultaneous method, the discriminant model of Unstandardized Canonical Discriminant Function (UCDF) can classify two groups of commercial banks based on their discriminant value by exactly 69.2% of the total sample or classification error of 30,8%. The result of research indicate from the six independent variables in this research, only 3 (three) variables have significance value <0,1 so it can sever liquidity level of commercial bank. Variables that can differentiate the liquidity level of the commercial banks are CAR (sig = 0.061), NPL (sig = 0.067) and NWC (sig = 0.074). CAR variable with the lowest significance value shows that the most dominant variable  sever the liquidity level of commercial banks listed BEI.